Bridging of oral anticoagulation with low-molecular-weight heparin: Experience in 373 patients with renal insufficiency undergoing invasive procedures - Hammerstingl, Christoph; Omran, Heyder; for the Bonn Registry of Alternative Anticoagulation to Prevent Vascular Events (Thrombosis and Haemostasis, 2009)
If surgery or another intervention is planned, current guidelines recommend bridging oral anticoagulation (OAC) with heparins in patients at elevated thromboembolic (TE) risk. While patients with renal impairment have a higher risk of bleeding and dosing of heparins is more difficult, there are no specific recommendations for bridging the latter patients. Hence, we aimed to investigate the efficacy and tolerability of using reduced low-molecular-weight heparin (enoxaparin) dosages for bridging of OAC. Three hundred twenty-two hospitalised and 51 ambulatory adult patients at moderate to high TE risk were enrolled. Patients with renal insufficiency (n=274 with creatinine clearance [CrCl] 30–50 ml/min and n=99 with CrCl 20–29 ml/min) received after discontinuation of OAC therapy enoxaparin 1mg/ kg once daily. Surgery was performed at international normalised ratio (INR) <1.5. Mean time between the last enoxaparin dose and procedure was 26.8 ± 2.7 hours. Within 30 days of individual follow-up, no case of TE was observed (0 %; 95 % confidence interval [CI] 0– 0.9). A total of 30 bleeding events (8.0 %; CI 5.5–11.3) occurred (3 major [0.8 %; CI 0.2–2.3] and 27 minor [7.2 %; CI 4.8–10.4]). Bleeding events occurred in 6.5% (CI 3.9–10.2) of patients with CrCl 30–50 ml/min and in 12.1% (CI 6.4–20.2) of patients with CrCl 20–29 ml/min (p between groups =0.08). Logistic regression analysis identified the CHADS2 score as the only independent haemorrhagic risk factor (p= 0.03). No heparin-induced thrombocytopenia (HIT-II) was reported. Bridging therapy could be performed in 51 (13.7%) ambulatory patients. In renally impaired patients undergoing bridging of OAC, the use of a priori reduced dosage of enoxaparin was not compromised by any TE events. It appeared well tolerated as the rate of major bleeds was low.
Keywords: Perioperative management; anticoagulation; low-molecular-weight heparin; thrombosis; bleeding; stratification; surgery; bridging; enoxaparin; register